Summer Academy - The Art of the Anthropocene Noah’s Arc Athens School of Fine Arts - Antoniou, Klitsa (My University, 2026)
The Art of the Anthropocene Noah’s Arc Athens School of Fine Arts Summer Academy Land Art at Limni Plastira Invited Tutor 8-27 July Organized by Katerina Athanasopoulou Greece